DAT-SPECT imaging in cases of drug-induced parkinsonism in a specialty movement disorders practice. (August 2018) - Yomtoob, Jacob; Koloms, Kimberly; Bega, Danny
Abstract: Objective: Compare clinical characteristics and outcomes in cases where DAT-SPECT imaging is used to distinguish Parkinson's disease from Drug-Induced Parkinsonsim. Background: Clinical uncertainty in diagnosing Parkinson's disease is common when patients are on dopamine-blocking medications. DAT-SPECT imaging can improve diagnostic certainty but little data are available on clinical characteristics and outcomes associated with normal and abnormal scan results. Methods: Retrospective chart review of patients seen at a movement disorders center between 2011 and 2017 where DAT-SPECT was ordered to distinguish Parkinson's disease from Drug-induced Parkinsonism. Descriptive statistics were calculated for variables of interest and compared by scan result. Chi-squared analyses was carried out for categorical variables and students' t-tests for continuous values. Results: 51 patients met inclusion criteria with 36 normal scans and 15 abnormal scans. Those with greater than 2 cardinal manifestations (tremor, rigidity, akinesia, postural instability) were more likely to have an abnormal scan (63.89% vs 93.33%, p = 0.04). No other clinical characteristics assessed were associated with scan results. Atypical antipsychotics (aripiprazole 39.21%, olanzapine 31.37%) and mood stabilizers (valproic acid 33.33%, lithium 17.65%) were most commonly associated with suspected Drug-induced Parkinsonism cases. A post-scan change in management occurred in 41.18% of patients. 55.56% of patients with normal scans responded to changes in the offending medication, with 16.66% taking over 3 months to show improvement. Conclusions: Many DAT-SPECT scans at our institution are ordered to distinguish Parkinson's disease from Drug-induced Parkinsonism because clinical characteristics alone are unreliable. DAT-SPECT results lead to changes in management and the outcomes of these changes are consistent with scan results. Highlights: DAT-SPECT scans are commonly ordered to distinguish PD from DIP. >2 cardinal features of PD correlated with abnormal DAT-SPECT scan results and raised suspicion for idiopathic PD. In general, historical and exam features cannot reliably distinguish all cases of PD from DIP. Atypical antipsychotics and mood stabilizers were most commonly implicated in DIP. DAT-SPECT results correlated with clinical management and outcomes.